A Secure Remote Mutual Authentication Scheme Based on Chaotic Map for Underwater Acoustic Networks - Shuailiang Zhang (IEEE Access, 2020)
Underwater acoustic networks (UANs) have emerged as a new wireless sensor network structure widely used in many applications. Sensor nodes are usually placed in a hostile and unattended underwater environment to gather information with limited resource. Since the underwater information is sensitive and special, only authenticated users have rights to get the information. The existing secure resource-constrained authentication schemes are not inapplicable for underwater acoustic networks, so a lightweight authentication scheme is the primarily task in underwater acoustic networks. In this paper, we present a chaotic maps remote user authentication and key agreement scheme for underwater acoustic networks based on the DLP and DHP, in which only authenticated users have rights to obtain the information. The proposed scheme applies the lightweight cryptographic primitives, such as one-way hash function and chaotic maps to accomplish mutual authentication and key agreement for underwater acoustic networks. The security of the proposed scheme is certified by applying the BAN logic and Random Oracle Model. Security analysis shows that our proposed scheme is safe and can meet ten security requirements and seven security goals. Performance analysis shows that our proposed scheme is more efficient compared with other resource-constrained schemes.